Handling radioactive wastes in the atomic energy program - U.S. Atomic Energy Commission (1949)
"This report describes radioactive waste materials, their sources in the atomic energy program, and the methods used on processing and storing or disposing of them at atomic energy installations and at laboratories and hospitals using radioisotopes. The appendices give more precise technical information on the research and development under way to bring about even greater safety, as well as to lower costs."
Keywords: Radioactive waste disposal; Radioactivity--Safety measures; Waste products